(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
Historiography has always neglected Caterina Visconti, whose political abilities were often disregarded due to gender bias. Nevertheless, the analyzed documents confirm her leadership, showing how Caterina was able to handle the succession using the civic symbology of Milan, despite going against the popolo, which was highly taxed. Its rebellion and the uprising of the Lombard cities, fighting for independence from the central power of the duke, made impossible for her to continue ruling, putting an end to the Regency. DOI 10.17464/9788867743339